A Base Cruck Aisled Hall at Frobury Farmhouse, Kingsclere, Hampshire. (1st January 2016) - Walker, John; Roberts, from Edward
Abstract : The core of Frobury Farmhouse, Kingsclere, Hampshire, is an aisled base cruck open hall built in c.1334/5d (Bridge and Miles, "Tree-Ring Dates from Oxford" (2015), 107) with a crown-post roof and passing braces in the closed trusses. Above all this is a full set of rafters from a mid-thirteenth-century aisled hall that had passing braces on all the trusses, tree-ring dated to 1263–8d, probably the predecessor to the base cruck hall. The 1334/5d arcade plates have edged halved and bridled scarf joints, the earliest tree-ring-dated example of these so far. These joints also show that all the arcade posts and the base cruck were erected first, before the arcade plates were laid from west to east on the north front arcade posts and from east to west on the rear posts.